Ketoreductase Catalyzed (Dynamic) Kinetic Resolution for Biomanufacturing of Chiral Chemicals - Huang, Chenming; Liu, Junling; Fang, Jiali; Jia, Xian; Zheng, Zhendong; You, Song; Qin, Bin (Frontiers in Bioengineering and Biotechnology, 2022)
Biocatalyzed asymmetric reduction of ketones is an environmentally friendly approach and one of the most cost-effective routes for producing of chiral alcohols. In comparison with the well-studied reduction of prochiral ketones to generate chiral alcohols with one chiral center, resolution of racemates by ketoreductases (KREDs) to produce chiral compounds with at least two chiral centers is also an important strategy in asymmetric synthesis. The development of protein engineering and the combination with chemo-catalysts further enhanced the application of KREDs in the efficient production of chiral alcohols with high stereoselectivity. This review discusses the advances in the research area of KREDs catalyzed asymmetric synthesis for biomanufacturing of chiral chemicals with at least two chiral centers through kinetic resolution (KR) approach and dynamic kinetic resolution (DKR) approach.